P908 Faecal Microbiota Transplantation refurbishes the crypt-associated microbiota in Ulcerative colitis. (30th January 2023) - Markandey, M; Bajaj, A; Verma, M; Virmani, S; Singh, M; Gaur, P; Das, P; Srikanth, C; Makharia, G; Kedia, S; Ahuja, V
Abstract: Background: Intestinal crypts form a pristine gut biogeographical niche, homing the intestinal stem cells and being the closest neighbors to underlying lamina propria. Initially believed to be sterile, the crypt lumen was recently shown to inhabit a conserved microbial population. However, the identity of the crypt-associated microbiota (CAM) remains elusive. The present study is among the first to illustrate the CAM composition in health and its deviation during ulcerative colitis (UC), and the effect of faecal microbiota transplantation along with an anti-inflammatory diet (FMT-AID) on the structure of this community. Methods: Recto-sigmoidal biopsies from controls, and from patients with mild-moderate UC before and after FMT-AID (n=26), were subjected to methacarn-fixation, followed by paraffin-embedding, sectioning and laser-capture microdissection-assisted crypt isolation. DNA isolated from micro-dissected samples was subjected to 16S rRNA gene sequencing. The bacterial presence in colonic crypts was confirmed using fluorescence in-situ hybridization(FISH). Microbiome data analysis was carried out by using QIIME2 and R packages. Results: FISH performed using pan-bacterial probes revealed the presence of sparse microbial clusters in colonic crypts, distinct from the overlying layer of Mucosa-associated microbiota (MAM), in both controls as well as in UC(Fig.1a and 1b). While MAM is dominated by members of phyla Firmicutes (45%) and Bacteroidetes (26%), CAM is comprised predominantly of aerobic members of Actinobacteria(54%) and Proteobacteria(38%), followed by minor proportions of Firmicutes(4%), Acidobacteria and Cyanobacteria (2% each). The significant members of CAM included aerobic genera - Cutibacterium (35%), Sphingobium (13%), Paracoccus (11%), Micrococcus (3%), Lawsonella (3%), Rothia (2%), Prauserella (2%), Kocuria, Corynebacterium, Acinetobacter and Brevundimonas (1% each)(Fig.1c and 1d). Analysis of CAM diversity in controls, and in patients with UC before and after FMT-AID, showed no significant alterations in the α- and β diversity matrices(Fig.1e and 1f).CAM demonstrated UC-associated dysbiosis of specific taxa which was restored after FMT-AID(Fig.2a and 2b). These FMT-restored CAM taxa correlated negatively with disease-associated parameters - Fecal calprotectin (FCP), Simple Clinical Colitis Activity Index (SCCAI) and Ulcerative Colitis Endoscopic Index of Severity (UCEIS)(Fig.2c and 2d). The positive effects of FMT-AID further refurbished the CAM-MAM interaction networks, which were obliterated in UC.(Fig.2e) Conclusion: A gut bacterial community, enriched in aerobic bacteria, resides in the colonic crypts, and undergoes taxa-level alterations during UC and in response to FMT.